ODNRI library has moved! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The library of ODNRI (Overseas Development Natural Resources Institute) has moved. This organization, recently created by combining the TDRI and LDRC, can now be contacted at the following address. ODNRI Central Avenue Chatham Maritime Chatham,...